Strategi Pengembangan Kompetensi Pegawai Melalui Teknologi Digital di Kantor Walikota Pekanbaru - Israwati; Nizamil Fadhli; Cintana Alivia Putri (Forum Kerjasama Pendidikan Tinggi, 2024)
The development of civil servants' (ASN) competencies through digital technology has become imperative in the era of globalization and digitalization, aligning with the Indonesian government's vision to realize a world-class bureaucracy. This study aims to analyze the strategy of employee competency development through digital technology in the Pekanbaru City Government, focusing on factors influencing the effectiveness of this strategy and its impact on employee performance and organizational effectiveness. Employing a quantitative approach with a survey method, this research involved 100 civil servant respondents in the Pekanbaru City Government. Data were collected through a structured questionnaire using a 5-point Likert scale. Data analysis was conducted using Structural Equation Modeling (SEM) or Partial Least Squares (PLS-SEM) to test the relationships between variables and mediation effects. The study concludes that the strategy of employee competency development through digital technology is an effective approach to improve employee performance and organizational effectiveness in the Pekanbaru City Government. Key recommendations include focusing on improving the quality of e-learning programs, investing in technological infrastructure and enhancing employees' digital competencies, and strengthening organizational support. These findings provide an empirical foundation for developing policies and practices for digital technology-based civil servant competency development in the era of bureaucratic transformation.